2016
DOI: 10.1088/0960-1317/26/6/065011
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of filling bismuth for x-ray absorption gratings through the enhancement of wettability

Abstract: Filling materials with high x-ray linear absorption coefficients in high aspect-ratio (HAR) structures is a key process for the fabrication of absorption gratings used in x-ray differential phase-contrast imaging. Bismuth has been chosen as an effective filling material in micro-casting technology, because of its low cost both in price and facility use. However, repellence on structure surfaces against molten bismuth leads to an obstacle in terms of completely filling bismuth into the small-aperture and HAR mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…The wetting properties of the liquid metal both on top and on the trench wall surface were extremely critical for uniformly filling the Si grooves. 4,7 This was demonstrated by a series of experiments with different metal alloys and metal coating of the Si gratings. When the liquid metal did not uniformly wet the Si surface, the metal was unequally distributed over the grooves, filling only some of them.…”
Section: A Metal Alloy Propertiesmentioning
confidence: 97%
See 1 more Smart Citation
“…The wetting properties of the liquid metal both on top and on the trench wall surface were extremely critical for uniformly filling the Si grooves. 4,7 This was demonstrated by a series of experiments with different metal alloys and metal coating of the Si gratings. When the liquid metal did not uniformly wet the Si surface, the metal was unequally distributed over the grooves, filling only some of them.…”
Section: A Metal Alloy Propertiesmentioning
confidence: 97%
“…2 Microcasting for X-ray absorption gratings has been developed by using molten Bi (melting temperature, 271 C) via capillary action and surface tension. [4][5][6] However, the low density (9.78 g/cm 3 , atomic number 83) of Bi requires much higher (factor of 1.7 at 30 keV) aspect ratio structures to get an absorption comparable to that of Au (density 19.32 g/cm 3 , atomic number 79). In a previous paper, 7 we demonstrated that metal microstructured optical elements for GI can be fabricated by using an alternative approach of Au-Sn microcasting into Si templates, which has the advantage of fast processing with a competitive cost and X-ray absorption only 20% less than pure Au (at an X-ray energy of 30 keV, see Table I).…”
Section: Introductionmentioning
confidence: 99%
“…As will be shown in the experimental section, this value can visualize small defects like cracks or waviness in the structure which are hardly seen in the reconstructed transmittance of the grating and difficult to quantify by microscopy-based surface analysis only. It also enables a quantitative, nondestructive and large area study of the lamellae inclination in grating fabrication processes where strong external forces [16,17] or thermal fluctuations [14,15] leading to mechanical deformations in the micrometer range have to be controlled.…”
Section: Local Absorber Inclinationmentioning
confidence: 99%
“…The filling of the absorber material can be performed by electroplating after deposition of plating contacts which seems to be the limiting factor in AR [11]. Other metalization techniques like Atomic Layer Deposition (ALD) [13], microcasting [14,15] or hot embossing [16,17] have been approached to increase AR and could possibly make the fabrication process simpler and more cost effective. Grating fabrication based on the LIGA (German acronym for Lithographie, Galvanoformung, Abformung) process, however, uses a conductive substrate with thick resist layers which are structured by DXRL.…”
Section: Introductionmentioning
confidence: 99%
“…33 Some researchers adopted a micro-casting approach to produce x-ray absorption gratings with bismuth at low cost. 34,35 In this paper, we present the first EI XPCI system built with metallic-glass masks fabricated by an imprinting machine. Also for the first time, Pt has been used as an excellent x-ray absorber in the fabrication of x-ray gratings for phase imaging purposes.…”
Section: Introductionmentioning
confidence: 99%